Pattern electroretinograms after cerebral hemispherectomy. - Azzopardi, P; King, S; Cowey, A (2001)
Cortically blind patients with brain damage restricted to the optic radiations or primary visual cortex may be able to detect and discriminate visual stimuli presented in their field defects, even though they deny seeing them. In contrast, patients who are hemianopic as a result of cerebral hemispherectomy cannot explicitly discriminate visual stimuli in their field defects, even when forced choice procedures are used. A possible explanation for this difference is that retrograde, transneuronal degeneration of the retina, which affects approximately 85% of wavelength-sensitive ganglion cells (approximately 70% of the total) after damage restricted to striate cortex, could be far more extensive after hemispherectomy, rendering the retina incapable of processing and conveying visual information to the brain. To test this, we assessed retinal ganglion cell function by means of electroretinography in three patients with cerebral hemispherectomy who were functionally blind. Steady-state pattern electroretinograms elicited by achromatic and isoluminant-chromatic (red-green) sinusoidal gratings, whose contrast was temporally modulated, were recorded from both blind and sighted hemiretinae. The electroretinograms were qualitatively indistinguishable from those of a control patient with a unilateral striate cortical lesion with documented visual capacity in his field defect. Within-subject analysis of variance revealed significant differences in the amplitude of the second harmonic (2f(0)) component of the averaged signal (diagnostic of retinal ganglion cell function) with respect to stimulus, but no significant differences between blind and sighted hemiretinae. This indicates that many retinal ganglion cells must have survived in the hemispherectomized patients. Isoluminant chromatic stimuli tended to elicit stronger signals than achromatic stimuli, which was unexpected given that wavelength-opponent Pbeta ganglion cells are far more susceptible than broad-band Palpha ganglion cells to transneuronal degeneration after cortical damage. It suggests that the 2f(0) component of the response to isoluminant chromatic stimuli might not reflect the activity of chromatic processes. Overall, the results show that the absence of residual vision in the blind fields of patients with cerebral hemispherectomy cannot be due to complete degeneration of retinal ganglion cells and, by extension, complete degeneration of their subcortical targets. This supports an alternative explanation, which is that intact extrastriate cortex is required for mediating voluntary responses to visual stimuli presented in the scotoma.